Practical Use of Derivatives in Different Engineering Fields - Praveen Shah; Suresh Kumar Sahani (Darul Yasin Al Sys, 2026)
This study examines the practical applications of derivatives as a cornerstone of engineering mathematics, enabling precise quantification of rates of change, optimization of processes, and accurate prediction of system behavior. It aims to demonstrate how derivatives are operationalized across mechanical, electrical, civil, chemical, aerospace, and computer engineering through motion analysis, structural integrity assessment, electrical circuit dynamics, chemical reaction rate calculations, flight stability analysis, and computational optimization. Employing case studies, mathematical models, and real-world examples, the paper systematizes the role of derivatives in formulating and solving engineering problems, supported by illustrative tables, formulas, and graphs that clarify key computational steps and outcomes. The findings highlight that derivatives provide a unifying analytical framework for modeling dynamic phenomena, improving design reliability, and enhancing control and optimization strategies across diverse engineering domains. The study concludes that a rigorous understanding and applied use of derivatives are essential for effective engineering analysis and decision-making, with implications for strengthening curricula in engineering mathematics and promoting derivative-based approaches in professional engineering practice.